Mycobacterium indicus pranii induces dendritic cell activation, survival, and Th1/Th17 polarization potential in a TLR-dependent manner - Kumar, Pawan (J Leukoc Biol, 2015)
MIP is a nonpathogenic, soil-borne predecessor of Mycobacterium avium. It has been reported previously that MIP possesses strong immunomodulatory properties and confers protection against experimental TB and tumor. DCs, by virtue of their unmatched antigen-presentation potential, play a critical role in activation of antitumor and antimycobacterial immune response. The effect of MIP on the behavior of DCs and the underlying mechanisms, however, have not been investigated so far. In the present study, we showed that MIP induces significant secretion of IL-6, IL-12p40, IL-10, and TNF-α by DCs and up-regulates the expression of costimulatory molecules CD40, CD80, and CD86. MIP(L) induced a significantly higher response compared with MIP(K). PI and Annexin V staining showed that MIP increases DC survival by inhibiting apoptosis. Consistently, higher expression of antiapoptotic proteins Bcl-2 and Bcl-xl was observed in MIP-stimulated DCs. Cytokines, produced by naïve T cells, cocultured with MIP-stimulated DCs, showed that MIP promotes Th1/Th17 polarization potential in DCs. Response to MIP was lost in MyD88(−/−)DCs, underscoring the critical role of TLRs in MIP-induced DC activation. Further studies revealed that TLR2 and TLR9 are involved in DC activation by MIP(L), whereas MIP(K) activates the DCs through TLR2. Our findings establish the DC activation by MIP, define the behavior of MIP-stimulated DCs, and highlight the role of TLRs in MIP-induced DC activation.